Tc-99m MDP Bone Scan Evaluation in Breast Cancer: A Study on 425 Patients - Hosen, MM Arif; Begum, Nasrin; Hossain, Mosharrof; Ahmed, Parvez; Mutsuddy, Pupree; Chowdhury, Sunny Anam (Medicine Today, 2018)
Breast cancer is the most frequent female cancer, especially in 'developed' countries. 30-85% of metastatic breast cancer patients will develop bone metastases during the course of the disease. The objective of this study was to evaluate the skeletal metastases in breast cancer patients by using Tc-99m MDP bone scan. A retrospective study was conducted on 425 consecutive female breast carcinoma patients referred for bone scan to Institute of Nuclear Medicine and Allied Sciences, Rajshahi from January 2015 to November 2017. Bone scan was performed by an intravenous bolus injection of 20 mCi Tc99m-MDP (technetium 99m methylenediphosphonate). Bone phase images were taken at three hours after injection of the radiotracer. Out of 425 patients, 290 patients (68.24%) had either normal bone scan or negative for skeletal secondaries and 135 patients (31.76%) were positive for skeletal metastases.Out of 135 positive bone scans 114 (84.44%) patients had multiple sites (two or more) and 21 (15.56%) patients had solitary site of bony involvement. Highest number of skeletal metastases was noted in thoraco-lumbar spine (81.48%). Other sites of metastases were in cervical spine (22.96%), pelvic bones (54.81%), ribs (40.74%), sternum (16.30%), scapula (19.26%), upper extremities (28.15%), lower extremities (36.30%), skull bone (12.60%) and clavicle (13.33%). Tc-99m MDP bone scan is very cost effective in comparison to other imaging modalities (CT, MRI, and PET) and play a major role in early detection of skeletal metastasis in breast cancer patients. Medicine Today 2018 Vol.30(2): 49-52